1993
DOI: 10.1111/j.1471-0528.1993.tb14304.x
|View full text |Cite
|
Sign up to set email alerts
|

Low dose aspirin in hypertensive pregnant women: effect on pregnancy outcome and prostacyclin‐thromboxane balance in mother and newborn

Abstract: Objective To study the effect of daily treatment with 50 mg of aspirin (ASA) on the hypertensive pregnancy complications and on the production prostacyclin (PGI2) and thromboxane A2 (TxA2) in high risk pregnant women and their infants. Design Placebo controlled prospective study. Setting Departments of Obstetrics and Gynaecology, University of Helsinki, University of Oulu and Central Hospital of Middle Finland, Finland. Subjects Two hundred and eight pregnant women with pre‐existing hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1
2

Year Published

1996
1996
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(15 citation statements)
references
References 24 publications
(56 reference statements)
0
12
1
2
Order By: Relevance
“…In this study, aspirin and dipyridamole did not prolong the bleeding time. Previous studies of patients receiving low-dose aspirin have reported prolonged bleeding time, which was not associated with clinical bleeding [15,16]. The explanation of this discrepancy is not clear, but it may be related to the lower dose of aspirin used in our study compared with other studies (40 mg vs 50-60 mg), different methods of measurement, and the small number of subjects in our study.…”
Section: Discussioncontrasting
confidence: 66%
“…In this study, aspirin and dipyridamole did not prolong the bleeding time. Previous studies of patients receiving low-dose aspirin have reported prolonged bleeding time, which was not associated with clinical bleeding [15,16]. The explanation of this discrepancy is not clear, but it may be related to the lower dose of aspirin used in our study compared with other studies (40 mg vs 50-60 mg), different methods of measurement, and the small number of subjects in our study.…”
Section: Discussioncontrasting
confidence: 66%
“…Low-dose aspirin has been proven to reduce the risk of pregnancy-induced hypertension (PIH) complicated with proteinuria (preeclampsia), and/or of intrauterine growth retardation, and to a lesser extent the risk of noncomplicated PIH, only in selected multiparous or mixed popula tions with a high risk of developing these complications [1][2][3][4][5][6] but not in nonselected populations with moderate risk as in the recent Italian study [7], In the pioneering study ofBeaufils et al [1] in multipa ras the selection criteria were severe vascular complica tions during the previous pregnancies (early precclampsia, in utero fetal death, abruptio placentae, pregnancy-in duced hypertension with small for gestational age (SGA) babies. The same type of criteria were used in the study of Benigni et al [2] and Uzan et al [3].…”
Section: P-human Chorionic Gonadotrophinmentioning
confidence: 99%
“…[28][29][30][31] A avaliação da redução do risco de restrição de crescimento fetal com o uso de aspirina foi definida como objetivo principal num estudo multicêntrico, publicado em 1991, o estudo EPREDA. 30 Concluiu que com a utilização entre as 15 -18 semanas de aspirina na dose de 150 mg, associada a dipiridamol (225 mg/dia) houve prevenção do risco de restrição de crescimento fetal, em grávidas com este antecedente.…”
Section: Methodsunclassified
“…Vinikka et al, 31 utilizando uma baixa dose (50 mg) de ácido acetilsalicílico iniciado em média às 15 semanas em mulheres com hipertensão arterial prévia à gravidez ou pré--eclâmpsia grave em gestação anterior, verificou que, em comparação com os controles, os agentes anti-plaquetá-rios não impediram a subida da pressão arterial materna, mas melhoraram os resultados fetais, com melhor resposta hemodinâmica fetal, redução de restrição de crescimento fetal e menor necessidade de internamento em unidades de cuidados intensivos neonatais. Verificaram uma forte inibição do tromboxano A2 materno, sem redução da produção de prostaciclina, preponderando portanto a dominância da ação vasodilatadora e de anti-agregação plaquetária.…”
Section: Methodsunclassified